WIFE PROTECTION OF VIOLENCE MEASURES IN HOUSEHOLD ACCORDING TO ISLAMIC LAW PERSPECTIVE - Dewi, Dian Kemala (Universitas Dharmawangsa Medan, 2020)
The results of this study are that Islam has governed the matter of the relationship between husband and wife who are bound in a domestic relationship if, without justifiable reasons a wife rejects the husband's request, then given Islamic law, the act is sinful. Therefore Islam considers that the rules contained in Law No. 23 of 2004 concerning the Elimination of Households specifically concerning sexual relations between husband and wife in line with Islamic law, then Islamic law considers these rules to be obeyed, otherwise if the rules in Law No. 23 of 2004 concerning the Elimination of Domestic Violence, contrary to Islamic law, Islamic law considers the issue unfit to follow. Domestic Violence can be charged with criminal penalties, while through non-penal policies, efforts will be made to prevent violence before the crime of domestic violence occurs.